ALMA characterizes the dust temperature of z ∼ 5.5 star-forming galaxies. Issue 3 (22nd August 2020) - Faisst, Andreas L; Fudamoto, Yoshinobu; Oesch, Pascal A; Scoville, Nick; Riechers, Dominik A; Pavesi, Riccardo; Capak, Peter
ABSTRACT: The infrared (IR) spectral energy distributions (SEDs) of main-sequence galaxies in the early Universe ( z > 4) is currently unconstrained as IR continuum observations are time-consuming and not feasible for large samples. We present Atacama Large Millimetre Array Band 8 observations of four main-sequence galaxies at z ∼ 5.5 to study their IR SED shape in detail. Our continuum data (rest-frame 110 μ m, close to the peak of IR emission) allows us to constrain luminosity-weighted dust temperatures and total IR luminosities. With data at longer wavelengths, we measure for the first time the emissivity index at these redshifts to provide more robust estimates of molecular gas masses based on dust continuum. The Band 8 observations of three out of four galaxies can only be reconciled with optically thin emission redward of rest-frame 100 μ m . The derived dust peak temperatures at z ∼ 5.5 (30\!-\!43 K ) are elevated compared to average local galaxies, however, 10 K below what would be predicted from an extrapolation of the trend at z < 4. This behaviour can be explained by decreasing dust abundance (or density) towards high redshifts, which would cause the IR SED at the peak to be more optically thin, making hot dust more visible to the external observer. From the 850-μ m dust continuum, we derive molecular gas masses between 10 10 and 10^11 M_ and gas fractions (gas over total mass) of 30\!-\!80 per cent (gas depletion times of 100\!-\!220 Myr ). All in all, our results provide a first measured benchmark SED to interpret future millimetre observations of normal, main-sequence galaxies in the early Universe.